The Context of Male Midwives Among Rural Communities - Savella, Marlou; Savella, Glicerio A. (ASEAN Journal of Community Engagement, 2022)
Midwifery is a profession that provides care for women, especially during pregnancy and childbirth. Despite the increasing number of men finishing a degree in midwifery, many people assume that only women can be midwives. Thus, this study aimed to identify the context of rural communities toward the practice of midwifery by men. Further, it explored the reasons for whether they will avail of the services of male midwives. The study was conducted on 14 women and four men residing in the rural areas of Ilocos Sur, Philippines. Respondents were accessed through purposive sampling based on the inclusion criteria: A researcher-made interview guide was used in obtaining qualitative data from the respondents. The responses were elicited through a semistructured, individual in-depth interview. Data collection was continued until data saturation was met. Ethical principles were followed throughout the process. Data were transcribed, coded, and categorized to obtain the results of the study. In this study, although male midwives are perceived as professionals and well trained, women still prefer female midwives and express their doubts about the men’s capability to provide care, especially during delivery and childbirth. The respondents also expressed feelings of embarrassment on showing their bodies to a man other than their husband or partner. On the contrary, their willingness to avail of their services depends on whether they can perform and provide quality care. From these findings, the Department of Health and local government units may increase the presence of male midwives by hiring them in different health facilities. This may eventually help them be well known and accepted in the healthcare profession.